Pregnancy and Postpartum Trends in Self‐Measured Blood Pressure and Derived Indices: The BOSHI Study - Seiya Izumi; Misato Nishimura; Noriyuki Iwama; Hasumi Tomita; Hirotaka Hamada; Taku Obara; Mami Ishikuro; Takahisa Murakami; Michihiro Satoh; Takuo Hirose; Masatoshi Saito; Takayoshi Ohkubo; et al. (The Journal of Clinical Hypertension)
ABSTRACT In this study, we aimed to reveal the trends of self‐measured blood pressure (SMBP) and SMBP‐derived indices during pregnancy and the postpartum period. The Babies and Their Parents Longitudinal Observation in Suzuki Memorial Hospital in the Intrauterine Period (BOSHI) Study is a prospective cohort study in Japan. Participants were instructed to measure SMBP daily during pregnancy and for 1 month after delivery. Among 237 participants with normotensive blood pressure (BP) during pregnancy and the postpartum period who were analyzed using mixed‐effects models for repeated measures, the SMBP was measured, on average, 14.3 times from the day before delivery to 28 days postpartum. The systolic blood pressure (SBP) and diastolic blood pressure (DBP) on the day before delivery were 110.6 ± 1.0 and 68.1 ± 0.8 mmHg (estimate ± standard error). Postpartum BP increased from postpartum Days 3–8 in SBP and from Days 3–22 in DBP, compared to that on the day before delivery. The SBP and DBP were 4.9 and 4.7 mmHg higher on postpartum Days 8 and 7 than the day before pregnancy, respectively. During pregnancy, the pulse rate (PR) showed an inverted U‐shaped trend and then sharply increased rapidly until the first postpartum day after delivery. The Shock Index showed a similar trend to that of the PR, decreased from labor until postpartum Day 8, and plateaued thereafter. The double product peaked during labor, remained higher than the prelabor levels for approximately 10 days, and then decreased in the postpartum period.